2021
DOI: 10.1128/msphere.00553-21
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Investigational MenABCWY Vaccine and of 4CMenB and MenACWY Vaccines Administered Concomitantly or Alone: a Phase 2 Randomized Study of Adolescents and Young Adults

Abstract: The bacterial species Neisseria meningitidis is a major cause of meningitis, with six meningococcal groups (serogroups) causing most cases. A licensed vaccine, MenACWY (Menveo), targets four of these meningococcal serogroups, and another vaccine, 4CMenB (Bexsero), targets serogroup B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Both 4CMenB and MenB-FHbp are components of pentavalent MenABCWY meningococcal vaccines under development [ 146 , 147 ] . While clinical studies evaluate immunogenicity and safety in younger adults (up to 25 years), these are reported as pooled data incorporating data from adolescents [ 148 , 149 ]. As such, at the present time, no additional insight into specific adult immunogenicity data can be drawn from these programmes.…”
Section: Menb Vaccinesmentioning
confidence: 99%
“…Both 4CMenB and MenB-FHbp are components of pentavalent MenABCWY meningococcal vaccines under development [ 146 , 147 ] . While clinical studies evaluate immunogenicity and safety in younger adults (up to 25 years), these are reported as pooled data incorporating data from adolescents [ 148 , 149 ]. As such, at the present time, no additional insight into specific adult immunogenicity data can be drawn from these programmes.…”
Section: Menb Vaccinesmentioning
confidence: 99%
“…Novel pentavalent vaccines are in clinical development. These include a pentavalent vaccine targeting MenX (i.e., MenACWY and X), principally to address MenW emergence in sub-Saharan Africa [114,115], and vaccines combining 4CMenB or MenB-FHbp vaccine components with MenACWY elements as MenABCWY formulations [116][117][118]. These pentavalent vaccines are in the latter stages of clinical development and could be available within the next 5 years.…”
Section: Additional Immunization Considerationsmentioning
confidence: 99%
“…Tapia et al suggested that the NmCV-5 pentavalent vaccine could provide immunity in toddlers after a single dose, without safety concerns. An investigational meningococcal ABCWY vaccine (MenABCWY) that is made up of components of vaccines against meningococcal serogroup B (4CMenB) and serogroups ACWY (MenACWY) is being developed; recent studies demonstrated its immunogenicity and its safety profile in adolescents [ 82 , 83 ].…”
Section: Looking To the Futurementioning
confidence: 99%